Recent Advances in Effective Reduction of Graphene Oxide for Highly Improved Performance Toward Electrochemical Energy Storage - Zhang, Peng; Li, Zhi; Zhang, Shijie; Shao, Guosheng (Energy & environmental materials (Hoboken, N.J.), 2018)
The demand for high‐quality graphene from various applications promotes the exploration of various synthesis methods such as chemical vapor deposition, chemical reduction of graphite oxide, liquid‐phase exfoliation, and electrochemical exfoliation. Among those, chemical treatments for the production of reduced graphene oxide (RGO) dictate the current technologies for mass production of graphene powder. However, such conventional chemical reduction methods are rather ineffective in removing oxygen‐containing functional groups from graphene oxide (GO), with resultant RGO products containing high level of structural defects. This leads to significantly damaged crystallinity and drastically lowered electric and thermal conductivity, which is probably the main bottleneck to limit the performance of RGO‐based materials. Great efforts such as thermal reduction, microwave‐irradiation reduction, or other novel reduction methods (e.g., photoreduction) have been developed to repair defects in RGO materials. This perspective review is to outline the latest advances toward effective reduction of GO for significantly enhanced properties. We demonstrate that effectively repaired RGO with large specific surface area and highly improved crystallinity is key to highly improved electric and thermal conductivity, thus leading to significantly enhanced properties essential for chemical energy storage devices.